Dynamic replanning: Some comments on the practical application of the analytical forecast - J. G. Kotzé; N. P. Du Preez (South African Journal of Business Management, 1984)
The importance of formal processes of planning and control in any organization has been recognized for the last two decades. Planning and replanning require some form of forecasting. Unfortunately, most forecasts utilized in practice consist of a complex mix of managerial expectations, organizational momentum, the predicted impact of managerial actions, as well as proposed managerial actions and good intentions. The evaluation of and control over such a forecast is difficult, if not impossible. This has led to efforts to analyse such a forecast into its major components. The practical implementation of these different forecast elements has yielded great success in planning applications. In control applications some undesirable side-effects have become apparent in recent years. A proposed modification to the control system application should eliminate such effects.
Keywords: 650